Abnormal large reaction cross sections for weakly bound nuclei at deep sub-barrier energies - Pakou, Athena; Palli, Konstantina (HNPS Advances in Nuclear Physics, 2026)
We review previous total reaction cross sections of weakly-bound projectiles at deep sub-barrier energies versus the reaction cross section of the mostly tightly-bound nucleus 4He on lead. Abnormal large reaction cross sections are traced at deep sub-barrier energies for the exotic nucleus 8B and the weakly-bound radioactive or stable 7Be and 6Li nuclei with ratios a million times higher than relevant results at barrier energies. The results are discussed.